2006
DOI: 10.1143/jjap.45.8188
|View full text |Cite
|
Sign up to set email alerts
|

Electron Impact Ionization of SiClx and TiClx (x = 1–4): Contributions from Indirect Ionization Channels

Abstract: We measured absolute partial cross sections for the formation of various singly charged positive ions produced by electron impact on SiCl x (x = 1–4) using two different experimental techniques, a time-of-flight mass spectrometer (TOF-MS) and a fast-neutral-beam apparatus. The energy range covered was from the threshold to 900 eV in the TOF-MS and to 200 eV in the fast neutral beam apparatus. In the case of SiCl4, the absolute cross sections obtained by the two different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 10 publications
(10 reference statements)
1
9
0
Order By: Relevance
“…Finally, since there is typically no bias applied for SiO 2 coating deposition, the sputter yield is not very high and, for the conditions under study in this paper, it could be concluded that ions do not have a significant influence on the deposition process and that sputtering effects are [17,20] e þ Si ! Si þ þ 2e s(E) [8] e þ SiO !…”
Section: Surface Reactions Included In the Modelmentioning
confidence: 82%
See 1 more Smart Citation
“…Finally, since there is typically no bias applied for SiO 2 coating deposition, the sputter yield is not very high and, for the conditions under study in this paper, it could be concluded that ions do not have a significant influence on the deposition process and that sputtering effects are [17,20] e þ Si ! Si þ þ 2e s(E) [8] e þ SiO !…”
Section: Surface Reactions Included In the Modelmentioning
confidence: 82%
“…Comparing these density profiles indicates a stepwise dissociation process from SiCl 4 towards SiCl in the bulk plasma. Indeed, it is more likely to create SiCl 3 from SiCl 4 , SiCl 2 from SiCl 3 and so on, abstracting only one Cl atom or Cl + ion each time . This explains the maxima of the densities of SiCl 1–3 since the gas is injected towards the center of the wafer and then disperses in the lateral direction.…”
Section: Resultsmentioning
confidence: 99%
“…From experimental side a few results are available [10][11][12][13][14] for these molecules. Comparisons are made of present results with experimental results and the theoretical results of DM formalism [10,12] and the CSP-ic model of Kothari et al [16].…”
Section: Discussionmentioning
confidence: 99%
“…Becker et al [11] have measured electron impact ionization of SiCl x (x=1-4) using a time-of-flight mass spectrometer (TOF-MS) and a fast-neutral-beam techniques. The energy range covered in the TOF-MS was from the ionization threshold to 900 eV and up to 200 eV in fast-neutralbeam apparatus.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation